Harmonious Family: Dynamics and Problems According to the Qur'an - Hikmatullah Hikmatullah; Tedy Subrata (International Journal of Islamic Educational Research, 2025)
Lately many problems in the family have emerged that are quite worrying, therefore the Qur'an emphasizes the importance of love, affection, and responsibility among family members. Along with the times, the structure and dynamics of the family have changed. Modern families may be made up of many forms, including nuclear families, extended families, single families, and even families formed through adoption. These changes are often influenced by broader social, economic, and cultural factors. This study aims to describe how the dynamics and problems in the family as well as the picture of a harmonious family in the perspective of the Koran. This research method uses a qualitative descriptive method. The conclusion of this study is to describe the dynamics and problems that occur in the family, conflicts in the family must be minimized to realize a balanced family and how to communicate in the family well. A balanced family is a family that is characterized by the harmony of the relationship (relationship) between father and mother, between father and child, and between mother and child. and the picture of a harmonious family from the perspective of the Koran, husband and wife have the responsibility to educate their children, maintain harmony in interactions between family members. The husband's responsibility related to family maintenance and children's education, as well as the seriousness of husband and wife in realizing harmony between them, according to the Qur'an, is an absolute requirement in building a sakinah family.